DETERMINATION OF GREENHOUSE GASES EMISSION QUANTIFICATION APPROACH FROM SOLID WASTE MANAGEMENT SYSTEM USING IPCC 2006 METHOD (CASE STUDY: CILACAP CITY) - FEBRIANTO, ARRY
Quantification method of greenhouse gases that widely used is IPCC 2006 (Intergovernmental Panel on Climate Change) by United Nations. Estimated method from IPCC consists of 3 tiers from tier 1 (standard method) to tier 3 (detailed method). The use of tier approach higher than tier 1 can reduce the uncertainty of the results. To increase tier and quantification results quality, the using of historical measurement data representatively and the measurement of quantification of IPCC 2006 parameters directly is needed. The study is aimed to analyze several quantifying parameters and predict greenhouse gases emission from waste management system of Cilacap City including waste treatment, transportation and disposal sector. Analysis of solid waste sample includes degradable organic carbon (DOC), DOC fraction (DOCf), degradation rate (kd) and methane fraction (F) analysis. Solid waste sample was divided into several categories that are traditional market waste, kitchen waste, garden waste, paper and bulk waste. Organic carbon measurements were determined by using open reflux method which refers to SMEWW 5220-C. DOC measurements were determined by hydrolysis with 70% sulfuric acid (11.5 M) at 100-105oC for 5-6 hours. The DOCf analysis was determined by measuring the temperature of solid waste anaerobic zone that was simulated with tube reactor for 30 consecutive days of incubation. Degradation rate was determined by measuring the difference of wasteÃ‚Â’s weight between beginning and after 30 consecutive days incubation. Methane fraction is determined by using methane gas container in SWDS and gas analyzer. The results of quantifying parameters of IPCC 2006 method for DOC bulk waste value is 0.48, DOCf value is 0.66, kd value is 0.18 and methane fraction is 0.37. Prediction of emission from waste treatment in Cilacap City in 2015 is 2.4 kg CH4 and 0.18 kg N2O. Prediction of emission from waste transportation in Cilacap City is 3,82x105 tonnes CO2; 20,1 tonnes CH4; and 20,1 tonnes N2O. Prediction of emission from waste disposal sector in Jeruklegi SWDS is 3,236 tonnes CH4.